Age-dependent fragility and life-cycle cost analysis of wood and steel power distribution poles subjected to hurricanes. Issue 8 (2nd August 2016) - Salman, Abdullahi M.; Li, Yue
Abstract: Power distribution systems are susceptible to damage from natural hazards, especially hurricanes. Hurricane winds can knock down distribution poles thereby causing power outages resulting in millions of dollars in lost revenue and restoration costs. Wood has been the dominant material used to support overhead lines in distribution systems in the US. Recently however, utility companies have been searching for cost-effective alternatives to wood due to environmental concerns, durability concerns and high cost of maintenance. Steel has emerged as a viable alternative to wood due to its advantages such as lower maintenance cost, light weight, consistent performance and invulnerability to insect attacks. Both wood and steel poles are prone to deterioration over time due to decay and corrosion, respectively. As utility companies increasingly adopt the use of steel poles, there is need for a comprehensive approach to compare the long-term reliability and cost-effectiveness of wood and steel poles. This study demonstrates a framework for comparing wood and steel poles subjected to hurricanes through fragility analysis that takes into account the strength deterioration over time. The framework also includes life-cycle cost analysis that incorporates fragility and strength deterioration. To demonstrate the framework, three locations in Florida, Virginia and Massachusetts were considered.